Parents' information needs during the first year at home with their very premature born child; a qualitative study - Monique Flierman; Daniel Bossen; Rosa de Boer; Eline Vriend; Fenna van Nes; Anton van Kaam; Raoul Engelbert; Martine Jeukens-Visser (Elsevier, 2024)
Objective: To obtain insights into parents' information needs during the first year at home with their very preterm (VP) born infant. Methods: We conducted semi-structured interviews with parents of VP infants participating in a post-discharge responsive parenting intervention (TOP program). Online interviews were audiotaped and transcribed verbatim. Inductive thematic analysis was performed by two independent coders. Results: Ten participants were interviewed and had various and changing information needs during the developmental trajectory of their infant. Three main themes emerged; (1) Help me understand and cope, (2) Be fully responsible for my baby, and (3) Teach me to do it myself. Available and used sources, such as the Internet, did not meet their information needs. Participants preferred their available and knowledgeable healthcare professionals for reassurance, tailored information, and practical guidance. Conclusion: This study identified parents' information needs during the first year at home with their VP infant and uncovered underlying re-appearing needs to gain confidence in child-caring abilities and autonomy in decision-making about their infants' care. Innovation: This study provides valuable information for healthcare professionals and eHealth developers to support parental self-efficacy during the first year after preterm birth.